Outcomes of Abdominal Wall Reservoir Placement in Inflatable Penile Prosthesis Implantation: A Safe and Efficacious Alternative to the Space of Retzius. (29th November 2013) - Stember, Doron S.; Garber, Bruce B.; Perito, Paul E.
Abstract Introduction Inflatable penile prosthesis (IPP) surgery is a successful therapeutic option for men with erectile dysfunction. Traditional placement of the reservoir in the retropubic space of Retzius is associated with the rare occurrence of significant complications including bladder, bowel, and vascular injury. An alternative site, posterior to the abdominal wall musculature, has been identified as a potentially safer location for reservoir placement. Aims The aim of this study was to describe our technique of abdominal reservoir placement during infrapubic IPP surgery and present our outcomes data. Methods We retrospectively reviewed our experience with abdominal reservoir placement during virgin IPP cases. Reservoirs placed anterior and posterior to transversalis fascia were analyzed separately. Main Outcome Measure The main outcome measures was assessment of reservoir‐related complications including palpable reservoir, reservoir herniation, and injuries to bowel, bladder, or major blood vessels. Results There were no injuries to bowel or major blood vessels with abdominal reservoir placement posterior or anterior to the transversalis fascia in properly segregated patients. Conclusion Abdominal reservoir placement is a safe and simple surgical method that can be recommended for most men undergoing IPP placement. Men with a history of pelvic surgery can have the reservoir placed between the rectus abdominis musculature and transversalis fascia, while other men can have the reservoir placed between transversalis fascia and peritoneum in order to avoid a palpable reservoir. By applying this protocol, the catastrophic injuries that occur rarely with retropubic reservoir placement can be reliably avoided. Stember DS, Garber BB, and Perito PE. Outcomes of abdominal wall reservoir placement in inflatable penile prosthesis implantation: A safe and efficacious alternative to the space of Retzius. J Sex Med 2014;11:605–612.